2018
DOI: 10.1155/2018/2785090
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Essential Fatty Acid Oxidation Cofactor Carnitine Is Stimulated in Heart and Liver after a Single Bout of Exercise in Mice

Abstract: We determined whether one single bout of exercise stimulates carnitine biosynthesis and carnitine uptake in liver and heart. Free carnitine (FC) in plasma was assayed using acetyltransferase and [14C]acetyl-CoA in Swiss Webster mice after 1 hour of moderate-intensity treadmill running or 4 hours and 8 hours into recovery. Liver and heart were removed under the same conditions for measurement of carnitine biosynthesis enzymes (liver butyrobetaine hydroxylase, γ-BBH; heart trimethyllysine dioxygenase, TMLD), org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Energy restriction, fasting state, and physical activity, can be associated with an elevated gene expression of OCTN2 in some tissues such as the liver and kidney; which in turn could lead to metabolism improvement. 14 , 58 Furthermore, L-carnitine reportedly enhances the efficacy of fatty acid metabolism by increasing non-oxidative glucose disposal. 59 Accordingly, L-carnitine supplementation can, conceivably, ameliorate the status of glycemic and lipid profile in patients with type 2 diabetes and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Energy restriction, fasting state, and physical activity, can be associated with an elevated gene expression of OCTN2 in some tissues such as the liver and kidney; which in turn could lead to metabolism improvement. 14 , 58 Furthermore, L-carnitine reportedly enhances the efficacy of fatty acid metabolism by increasing non-oxidative glucose disposal. 59 Accordingly, L-carnitine supplementation can, conceivably, ameliorate the status of glycemic and lipid profile in patients with type 2 diabetes and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Ringeis et al [17] demonstrated that 12 weeks of HF feeding with moderate intensity of ET increased PPAR-α mRNA expression in gastrocnemius muscle without producing a concomitant change in the expression of OCTN2. This is in contrast with the effects observed with acute high intensity exercise, in which increases in PPAR-α protein in kidney, liver, and heart were associated with accompanying increases in OCTN2 expression [16,17]. Similar responses were reported following 10 weeks of twice daily treadmill running in rat kidney and liver [14].…”
Section: Discussionmentioning
confidence: 49%
“…PPARα is a ligand-activated transcription factor that stimulates hepatic and renal gene expression of γ-BBH, OCTN2, and carnitine palmitoyltransferase-I (CPT-1) to enhance mitochondrial FA oxidation [8,9,12,13]. We have shown that expression of γ-BBH and OCTN2 is increased in rat and mouse tissue in response to acute and chronic exercise training (ET), with both conditions stimulating carnitine biosynthesis and increasing the levels of plasma carnitine [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic carnitine can be obtained from the diet, can be locally biosynthesized, or can originate from tissue redistribution. Carnitine biosynthesis is higher in conditions in which rates of β-oxidation are chronically elevated 39,40 . Negligible accumulation of (long-chain) acylcarnitine species, seen in the livers of both cIMF and eIMF-fed mice, implies that β-oxidation does not outpace the TCA cycle in this tissue 29,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Higher protein levels of TCA cycle enzymes may correspond with a higher TCA cycle flux. The concomitant higher levels of proteins involved in β-oxidation 38 and the higher hepatic carnitine concentration are suggestive of higher β-oxidation activity 39,40 . An increased flux through the β-oxidation cycle, also yielding more acetyl-CoA, would then require a higher flux through the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%